STEADY RESPONSES OF ROD UNDER ECCENTRIC AXIAL LOADING - ZHANG Ping (Jixie qiangdu, 2020)
The pull rod under eccentric loading exists extensively in engineering project,the computations of its stress and strength directly affect its reliability,especially its dynamic stress computations. The elastic dynamic mechanics were used here to study the computations of the bending stress and axial stress of the eccentric loaded rod under steady force,and the analytic expressions were given,numerical example was provided to show the variations of the amplitude of the bending stress and axial stress with the disturbance frequency,the theoretical analyses and the computation results of given example show that the amplitude of the bending stress and axial stress obviously depend on the disturbance frequency,which is different from that of corresponding static problems. The analyses and conclusions given here have some references to the dynamic reliability design.